The Parliament Control on Ombudsman Institution (Journal of Legal Studies, 2017)
The Parliamentary control is exerted not only on the Government but also on some autonomous administrative authorities and on some special bodies under its subordination. The constitutional norms are extremely synthetic on this form of parliamentary control, as only the art. 116 par. 2 of the Constitution stipulates that specialised bodies may be established which to function under Government subordination or as autonomous administrative structures, by organic law. The Ombudsman Institution is an autonomous administrative authority established according to the Constitutional provisions, the activity of which is under Parliament control. For the first time, the Ombudsman has been established in Sweden as additional tool to the control exerted by the Parliament on the executive power. Additional guarantees were enforced by it, as being an institution with democratic character, for the defence of the rule of law and for the protection of the individual rights and freedoms. On the Ombudsman‟s appointment and role, the article 58 of the 1991 Romanian Constitution stipulates that the person in charge is to be appointed by the Chamber of Deputies and the Senate in joint meeting, its appointment being of five years and that the Ombudsman cannot have another civil or private service except for the teaching positions in higher education.